Women Capacity, Community Resilience and Sustainable Post Disaster Reconstruction: Case Study from Indonesia - Yumarni, Tri (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
This paper aims to flesh out women capacity for creating community resilience and practices of sustainable post disaster reconstruction in Bantul district Central Java Indonesia. Based on case study, the findings show women grassroots organizations have insight, information, experience, networks and resources vital within earthquake reconstruction as such capacities increasing resilience. During reconstruction women demonstrated their capacity as income-earners, producers and managers of food production, providers of clean water and fuel, and participants in village voluntary labors for maintaining public infrastructures and environments.Â